2017
DOI: 10.1016/j.ydbio.2017.06.020
|View full text |Cite
|
Sign up to set email alerts
|

BmpR1A is a major type 1 BMP receptor for BMP-Smad signaling during skull development

Abstract: Craniosynostosis is caused by premature fusion of one or more sutures in an infant skull, resulting in abnormal facial features. The molecular and cellular mechanisms by which genetic mutations cause craniosynostosis are incompletely characterized, and many of the causative genes for diverse types of syndromic craniosynostosis have not yet been identified. We previously demonstrated that augmentation of BMP signaling mediated by a constitutively active BMP type IA receptor (ca-BmpR1A) in neural crest cells (ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

6
0

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 58 publications
(86 reference statements)
0
23
0
Order By: Relevance
“…Next, we also measured the sagittal length of the two most anterior bones: the nasal and the frontal bones. We previously reported that both bones are shorter in the caA3 mutant mice in association with a wider distance between the eyes (hypertelorism) (Komatsu et al, ; Pan et al, ). Similar to the distances between bones, nasal bone length and distance between eyes were significantly rescued in the mutant mice in Tx 2 and Tx 3 groups but not in the Tx 1 treatment group (Figure D).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Next, we also measured the sagittal length of the two most anterior bones: the nasal and the frontal bones. We previously reported that both bones are shorter in the caA3 mutant mice in association with a wider distance between the eyes (hypertelorism) (Komatsu et al, ; Pan et al, ). Similar to the distances between bones, nasal bone length and distance between eyes were significantly rescued in the mutant mice in Tx 2 and Tx 3 groups but not in the Tx 1 treatment group (Figure D).…”
Section: Resultsmentioning
confidence: 94%
“…We used our previously generated transgenic mice that conditionally express a constitutively active form of Bmpr1a ( caBmpr1a , aka caAlk3 ) that develop craniofacial abnormalities including craniosynostosis when crossed with P0 ‐cre mice that express a Cre‐recombinase in a neural crest‐specific promoter (caA3 mutant hereafter) (Hayano, Komatsu, Pan, & Mishina, ; Kamiya et al, ; Komatsu et al, ; Pan et al, ; Yamauchi et al, ). These mice developed premature fusion of cranial sutures including the nasal and the anterior frontal sutures before weaning stage along with a large osseous defect at the level of the posterior frontal suture (Supporting Information Figure 1) (Komatsu et al, ; Pan et al, ). To identify the effect of enhanced BMP signaling on the mesenchymal stem cell population that gives rise to the cranial suture (Zhao et al, ), these mice were crossed with a Gli1 ‐LacZ mouse line, which expresses LacZ in Gli1 expressing cells (Bai, Auerbach, Lee, Stephen, & Joyner, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BMPRII is constitutively active and can phosphorylate and activate BMPRI upon ligand binding. All the BMPRI molecules, BMPRIA, BMPRIB and ACVR1, have been shown to contribute to skeletal development 15 , 18 – 21 . It has been reported that Bmpr1a , when overexpressed, successfully rescues the differentiation defect of chondrocytes due to deletion of Bmpr1b 22 , suggesting that they have redundant functions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed vital roles of BMPs and their receptors in osteoblast and chondrocyte differentiation and bone formation during skeletal development 11 , 16 , 18 , 23 . Conventional knockout mice for Bmpr1a show early embryonic lethality 24 .…”
Section: Introductionmentioning
confidence: 99%